Pengaruh Nilai Tukar, Inflasi, Suku Bunga Bi Dan Dow Jones Index Terhadap Indeks Harga Saham Gabungan Di Bursa Efek Indonesia Periode 2018-2022 - Syarifuddin, Ahmad; Yusroni, Nanang (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The development of financial asset investment in the capital market is growing quite rapidly, starting from the ease of making sales and purchases but also the low capital required to start investing in the capital market. However, in the capital market, especially the stock exchange, it is an investment instrument that has a high risk and high return, so investors must be selective in determining which share issuer to buy by considering factors that can influence share prices on the Indonesian Stock Exchange. Some of them include exchange rates, inflation, BI interest rates and the Dow Jones index. Therefore, this research was carried out to analyze the influence of exchange rates, inflation, BI interest rates and the Dow Jones index on the composite stock price index in 2018-2022 with the data used being a monthly time series with a sample size of 60 months. This research uses a quantitative approach with the analytical techniques used in this research, namely descriptive statistical analysis, classical assumption tests and multiple linear regression tests which were processed using the E-Views version 12 program. With results showing that the exchange rate has a significant negative effect on the stock price index combined, then for inflation, BI interest rates and the Dow Jones index there is a partially significant positive influence on the composite stock price index on the Indonesia Stock Exchange.